Grundsteuerreform. Ende einer Odyssee? - Löhr, Dirk (Springer, 2017)
Im September 2016 hatten die Finanzminister der Länder ein Modell für die Reform der Grundsteuer auf den Weg gebracht. Sie war notwendig geworden, nachdem der Bundesfinanzhof die alten Einheitswerte als Bemessungsgrundlage für die Grundsteuer verworfen hatte. Nach Widerstand aus Bayern und Hamburg wurde das Gesetzesvorhaben ausgesetzt und muss in der neuen Legislaturperiode wieder angestoßen werden. Es werden verschiedene Reformmodelle in Hinblick auf die Belastung unterschiedlicher Gebäudetypen und ungenutzter Grundstücke untersucht.

Due to the resistance of Hamburg and Bavaria, the last draft legislation for a property tax reform failed, which was launched by the Federal Council of the German states in autumn of 2016. Since the constitutional court is expected to declare the existing tax assessment rules as unconstitutional, the existing property tax might be suspended, if the property tax cannot be revised on time after the federal elections. With this background, the article first analyses feasible reform options. Moreover, for the first time, an exemplary analysis of the tax payable of these alternative models is provided for two different cities, in terms of their spatial economic structures. A proposal for a corresponding reform of the financial equalisation scheme is forwarded also.
Keywords: Steuer; Grundsteuer; Bemessungsgrundlage; Steuerreform